Recent advances in the analysis of metal hyperaccumulation and hypertolerance in plants using proteomics - DalCorso, Giovanni; Fasani, Elisa; Furini, Antonella (Frontiers in Plant Science, 2013)
Hyperaccumulator/hypertolerant plant species have evolved strategies allowing them to grow in metal-contaminated soils, where they accumulate high concentrations of heavy metals in their shoots without signs of toxicity. The mechanisms that allow enhanced metal uptake, root-to-shoot translocation and detoxification in these species are not fully understood. Complementary approaches such as transcriptomic-based DNA microarrays and proteomics have recently been used to gain insight into the molecular pathways evolved by metal hyperaccumulator/hypertolerant species. Proteomics has the advantage of focusing on the translated portion of the genome and it allows to analyze complex networks of proteins. This review discusses the recent analysis of metal hyperaccumulator/hypertolerant plant species using proteomics. Changes in photosynthetic proteins, sulfur and glutathione metabolism, transport, biotic and xenobiotic defenses as well as the differential regulation of proteins involved in signaling and secondary metabolism are discussed in relation to metal hyperaccumulation. We also consider the potential contribution of several proteins to the hyperaccumulation phenotype.